2020
DOI: 10.1104/pp.20.00144
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Wall-Associated Kinase SlWak1 Depends on Fls2/Fls3 to Promote Apoplastic Immune Responses to Pseudomonas syringae

Abstract: Wall-associated kinases (Waks) are important components of plant immunity against various pathogens, including the bacterium Pseudomonas syringae pv. tomato (Pst). However, the molecular mechanisms of their role(s) in plant immunity are largely unknown. In tomato (Solanum lycopersicum), wall-associated kinase 1 (SlWak1), has been implicated in pattern recognition receptor (PRR)-triggered immunity (PTI) because its transcript abundance increases significantly after treatment with the flagellin-derived, microbe-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 63 publications
3
54
0
Order By: Relevance
“…The presumed orthologs of BAK1 in tomato are Serk3A/Serk3B, but this has not been experimentally investigated. Additionally, Fls2 and Fls3 both coimmunoprecipitate with Wak1 independently of flg22/ flgII-28 or Arabidopsis BAK1 (Zhang et al, 2020a). It is possible that Fls3 and Fls2 may interact differently with the Serks, and that will be a focus of future studies.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The presumed orthologs of BAK1 in tomato are Serk3A/Serk3B, but this has not been experimentally investigated. Additionally, Fls2 and Fls3 both coimmunoprecipitate with Wak1 independently of flg22/ flgII-28 or Arabidopsis BAK1 (Zhang et al, 2020a). It is possible that Fls3 and Fls2 may interact differently with the Serks, and that will be a focus of future studies.…”
Section: Discussionmentioning
confidence: 93%
“…Fls2 and Fls3 appear to contribute equally to PTI, which suggests that they may use some similar mechanisms and/or signaling pathways. In fact, we reported recently that activation of the Fls2 or Fls3 pathways induces the expression of the wall-associated kinase Wak1 gene, and both PRRs coimmunoprecipitate with the Wak1 protein, which appears to act independently of ROS production and at a later stage of PTI (Zhang et al, 2020a). However, the differences in several readouts from the Fls2 and Fls3 pathways also suggest underlying differences in some aspect of their functions.…”
Section: Discussionmentioning
confidence: 95%
“…Wounding induced WAK-RLKs maybe as an injury signal receptor quickly participated in plant defense response paralleled or combined with other RLKs pathway. Recently, Zhang et al found tomato SlWAK1 (named SlWAK4 in our study) coimmunoprecipitated with both pattern recognition receptors Fls2 and Fls3, acting in a complex and playing an important role during later stages of pattern-triggered immunity in the apoplast [ 19 ].…”
Section: Discussionmentioning
confidence: 93%
“…For example, SlWAK5 , SlWAK6, SlWAK7, and SlWAK8; SlWAKL6, SlWAKL7, SlWAKL8, SlWAKL9, SlWAKL10, SlWAKL11, and SlWAK12 have the same motifs respectively. This phenomenon indicates that genes from the same cluster may share extremely similar functions [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation